A general framework for greedy routing in mobile ad-hoc networks - Al-shugran, Mahmoud; Ghazali, Osman; Hassan, Suhaidi (2012)
This paper introduces the notion of a reliable and efficient greedy routing provisioning (RGRS) in mobile ad hoc networks.The proposed RGRS constructed of two mechanisms in the context of improving and enhancing greedy routing.These mechanisms are Dynamic Beaconing Update Mechanism (DBUM), and Dynamic and Reactive Reliability Estimation with Selective Metrics (DRESM).The building structure of DRESM is based on the notion of multi-criteria next relay node selection using fuzzy weighted logic multi-objectives.To efficiently track node's status, DRESM is supported with a dynamic and effective updating DBUM scheme.In this work, and to show the performance of the proposed RGRS detailed experiments in simulated environments are executed.The simulation results show that RGRS is quite reliable and efficient and superior to the traditional greedy forwarding strategy (GFS). Moreover, the results reveal that RGRS can be used as a standalone routing protocol without the aid of any recovery mode.RGRS outperforms GFS in terms of the packet delivery ratio. Moreover, RGRS achieves high level of accuracy in terms of nodes’ information and can find routs between communicating nodes whose cost is close to the optimum.